RESPON VARIETAS PADI IR64 DAN IR64-SUB 1 TERHADAP PERENDAMAN DAN PEMUPUKAN N - Ikhwani Ikhwani; Gagad R Pratiwi; Abdul Karim Makarim (Jurnal Ilmu Tanah dan Lingkungan, 2019)
There are many new rice varieties have been produced, introduced and breed at IRRI and the other National Agriculture Research Institutes that are tolerance to submergence condition to anticipate global warming and flash flooding around theworld. Among others are IR64-Sub 1, Suwarna-Sub 1, Inpara-1, Inpara-2, inpara-3 etc. However, those new varieties have not been tested widely yet, and the method of rice cultivation under submergence condition have not been adjusted, including the nutrient management.A greenhouse experiment was conducted at Muara Research Station, Bogor during 2008 dry season. The objectives of this experiment are (1) to study the effects of time of submergence and N application on plant growth and yield of  R64 and IR64-Sub 1 rice varieties; (2) to find the best nutrient management for submergence rice varieties. The experiment was conducted during 2008 dry season at greenhouse, Muara Research station, Bogor. The design of the  experiment was a Completely Randomized Factorial Design with three eplications. Factor 1 is rice variety (IR64 and IR64-Sub 1); Factor 2 is time of submergence (without submergence or control, submergence at vegetative phase (15 to 25 d.a.t), and at generative phase (35 to 45 d.a.t)). Factor 3 is N application, namely (F1) 300 kg Urea/ha 3x applications at 7 d.a.t- 30 d.a.t – 55 d.a.t; (F2) Mudball urea –300 kg Urea/ha applied once at 7 d.a.t. (F3) compost; and (F4) compost and urea; (F5) Urea and silikat.urea-N application at four time 0 d.a.t – 7 d.a.t – 30 d.a.t – 55 d.a.t (factor C). The results of experiments showed that submergence changes rice plant growth pattern (mainly tiller number and plant height), increased dry grain weight of IR64, namely 35.9 g at early vegetatif phase and 29.9 g at late vegetatif phase, while for IR64-Sub 1 32.6 g and 30.3 g at the same respective phase. Mudball urea and silicate application improved plant resistant to submergence and increase rice yield.